Desain Multimedia E-Learning Berbasis Learning Management System Sebagai Media Pembelajaran Siswa SMK dalam Praktik Kerja Industri - Mira Sartika (CV. Multi Kreasi Media, 2022)
This study aims to examine the use of e-learning media based on a learning management system (LMS) in the industrial work practices of vocational high school students. This research uses Research and Development (R&D) research procedures, which is a process to develop a new product or improve an existing product, which can be accounted for. This research is generally carried out using three research stages, namely the preliminary study stage, the model development stage, and the model test stage. Data collection techniques used interview sheets, expert validation questionnaires, student responses, and tests conducted before and after learning. The results of this study indicate that the feasibility of the resulting e-learning multimedia is included in the very feasible category according to chemistry learning materials experts and media experts, namely 97% and 83%, respectively. So, it is suggested that teachers can use and develop interactive multimedia as a technology-based learning strategy according to student needs.